2016
DOI: 10.1155/2016/8324925
|View full text |Cite
|
Sign up to set email alerts
|

Duplicate Vas Deferens Encountered during Inguinal Hernia Repair: A Case Report and Literature Review

Abstract: Duplication of the vas deferens is a rare anomaly, defined as the presence of two distinct vasa deferentia within one spermatic cord, with only 28 cases reported worldwide since 1959. We report the case of a 63-year-old man with a duplicate vas deferens, presenting with abdominal pain from bowel obstruction secondary to incarcerated inguinal hernia. Spermatic cord dissection during hernioplasty revealed duplication of the vas deferens within the right spermatic cord. Doppler ultrasonography confirmed absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…After that, only 28 cases of duplicated vas deferens of different age groups ranging from 7 months to 75 years have been mentioned. It is interesting that most of the cases have been accidentally discovered during inguinal operations rather than clinical evaluation such as orchiopexy (32%), inguinal hernia repair (23%), and other operations such as vasectomy, varicocelectomy, radical prostatectomy or even in postmortem cadavers (Breitinger et al, ; Lee, Kim, Kim, & Chung, ; Shariat, Naderi, Miles, & Slawin, ; Sirasanagandla, Nayak, Jetti, & Bhat, ). Concerning laterality, it has been mentioned that right‐sided, left‐sided and bilateral duplication occurred equally; unilateral duplication is twice as common as bilateral duplication (Liang, Subramanian, Weedin, Griffith, & Awa, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, only 28 cases of duplicated vas deferens of different age groups ranging from 7 months to 75 years have been mentioned. It is interesting that most of the cases have been accidentally discovered during inguinal operations rather than clinical evaluation such as orchiopexy (32%), inguinal hernia repair (23%), and other operations such as vasectomy, varicocelectomy, radical prostatectomy or even in postmortem cadavers (Breitinger et al, ; Lee, Kim, Kim, & Chung, ; Shariat, Naderi, Miles, & Slawin, ; Sirasanagandla, Nayak, Jetti, & Bhat, ). Concerning laterality, it has been mentioned that right‐sided, left‐sided and bilateral duplication occurred equally; unilateral duplication is twice as common as bilateral duplication (Liang, Subramanian, Weedin, Griffith, & Awa, ).…”
Section: Discussionmentioning
confidence: 99%
“…Duplications of vas deferens are not uncommon; however, only about 28 cases have been reported in the literature prior to ours mostly discovered accidentally during inguinal surgeries as in hernia repair, vasectomy, orchiopexy and varicocelectomy. The exact etiopathogenesis of such anomaly is not well established; however, most of the studies suggested that it may result from either duplication or a transversal division of the central portion of the mesonephric duct during embryogenesis (Breitinger, Roszkowski, Bauermeister, & Rosenthal, ). In addition, duplications of vas deferens could be either “unilateral or bilateral,” “segmental or complete,” “isolated or associated with other anomalies especially renal ectopy or hypogenesis or agenesis.” Thus, recognition and proper assessment of this anomaly are important to exclude associated renal anomalies and to avoid injury to the vas deferens or an ineffective vasectomy procedure (Chintamani, Tandon, & Kumar, ).…”
Section: Introductionmentioning
confidence: 99%
“…Duplicate vas deferens is a rare abnormality. It is the presence of two separate vasa deferentia within one spermatic cord and is rarely reported in literature worldwide [2] [3]. It has been encountered during inguinal hernia repair, orchidopexy, varicocoelectomy, vasectomy and radical prostatectomy [4].…”
Section: Introductionmentioning
confidence: 99%
“…Duplication of the vas deferens is a rare congenital anomaly of the male reproductive system, with an estimated incidence of approximately 0.05%. 1 Vas deferens duplication is often an incidental finding during surgeries involving the spermatic cord, such as inguinal hernia repair, varicocelectomy, orchidopexy, and vasectomy. 2 Embryologically, the proximal vas precursor is a segment along the mesonephric duct, located at an intermediate position between the upper and common mesonephric ducts.…”
Section: Introductionmentioning
confidence: 99%
“…A double vas deferens, an ectopic ureter draining into the ejaculatory system, is sometimes mistakenly called a duplicated vas deferens. [1][2][3] Recognition of a duplicated vas deferens is vital to prevent trauma and iatrogenic injury during surgical procedures. We present the case of a young male diagnosed with bilateral inguinal hernia who was found to have a duplicated vas deferens.…”
Section: Introductionmentioning
confidence: 99%